Penerapan Etika Bisnis Islam Dalam Transaksi Jual Beli Sembako Di Pasar Manukan - Iftitah, Anggi; Zakariya, Novie Andriani (Journal of Islamic Management, 2025)
The high amount of market demand, especially during Ramadan, for basic food needs has increased the business of grocery stores, but not many shop owners understand Islamic business ethics in buying and selling transactions. This study aims to determine the application of Islamic business ethics in buying and selling merchandise transactions in Manakan Market, Surabaya. The research method used in this study is descriptive qualitative research method. While the data collection technique used in this study was to use observation and interview techniques. The results of this study itself show that the application of Islamic business ethics in buying and selling merchandise transactions in Manukan Market follows and applies Islamic business ethics in accordance with the principles or values of Islamic teachings based on the Qur'an and Hadith.